When people start getting real: The Group Living Skills Survey for extreme work environments - Landon, Lauren Blackwell; Miller, Jennifer C. W.; Bell, Suzanne T.; Roma, Peter G. (Frontiers in Psychology, 2024)
Introduction: Group living skills, that is, being tidy and considerate of others, are an important skillset for teams who live and work together. However, this construct does not have a validated measure to enable understanding of how group living skills influence team dynamics over time. We developed and validated a short measure of group living skills for teams living in extreme work environments. Methods: We collected data across 83 individuals in 24 teams living and working in space and spaceflight analog environments on missions of 45-to 240-days. Results: We provide evidence of reliability and validity for the GLS Survey over time and identify a twofactor structure. We also demonstrate its use as a measure of team-level dynamics as well as its utility as a sociometric measure to identify a person's degree of group living skills. Discussion: We outline recommendations for how to use this new measure in future research and applied settings to understand this unique aspect of teams living and working together.